Design and baseline findings of a large‐scale rapid response to an HIV outbreak in people who inject drugs in Athens, Greece: the ARISTOTLE programme. (14th July 2015) - Hatzakis, Angelos; Sypsa, Vana; Paraskevis, Dimitrios; Nikolopoulos, Georgios; Tsiara, Chrissa; Micha, Katerina; Panopoulos, Anastasios; Malliori, Meni; Psichogiou, Mina; Pharris, Anastasia; Wiessing, Lucas; van de Laar, Marita; et al.
Abstract Aims To (i) describe an intervention implemented in response to the HIV‐1 outbreak among people who inject drugs (PWIDs) in Greece (ARISTOTLE programme), (ii) assess its success in identifying and testing this population and (iii) describe socio‐demographic characteristics, risk behaviours and access to treatment/prevention, estimate HIV prevalence and identify risk factors, as assessed at the first participation of PWIDs. Design A 'seek, test, treat, retain' intervention employing five rounds of respondent‐driven sampling. Setting Athens, Greece (2012–13). Participants A total of 3320 individuals who had injected drugs in the past 12 months. Intervention ARISTOTLE is an intervention that involves reaching out to high‐risk, hard‐to‐reach PWIDs ('seek'), engaging them in HIV testing and providing information and materials to prevent HIV ('test') and initiating and maintaining anti‐retroviral and opioid substitution treatment for those testing positive ('treat' and 'retain'). Measurements Blood samples were collected for HIV testing and personal interviews were conducted. Findings ARISTOTLE recruited 3320 PWIDs during the course of 13.5 months. More than half (54%) participated in multiple rounds, resulting in 7113 visits. HIV prevalence was 15.1%. At their first contact with the programme, 12.5% were on opioid substitution treatment programmes and the median number of free syringes they had received in the preceding month was 0. In the multivariable analysis, apart from injection‐related variables, homelessness was a risk factor for HIV infection in male PWIDs [odds ratio (OR) yes versus no = 1.89, 95% confidence interval (CI) = 1.41, 2.52] while, in female PWIDS, the number of sexual partners (OR for > 5 versus one partner in the past year = 4.12, 95% CI = 1.93, 8.77) and history of imprisonment (OR yes versus no = 2.76, 95% CI = 1.43, 5.31) were associated with HIV. Conclusions In Athens, Greece, the ARISTOTLE intervention for identifying HIV‐positive people among people who inject drugs (PWID) facilitated rapid identification of a hidden population experiencing an outbreak and provided HIV testing, counselling and linkage to care. According to ARISTOTLE data, the 2011 HIV outbreak in Athens resulted in 15% HIV infection among PWID. Risk factors for HIV among PWID included homelessness in men and history of imprisonment and number of sexual partners in women.